2018
DOI: 10.1007/s12011-018-1243-z
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Cytoprotective Activity of Oxydiacetate Complexes of Cobalt(II) and Nickel(II) with 1,10-Phenantroline and 2,2′-Bipyridine

Abstract: The antioxidant properties of oxydiacetate complexes of cobalt(II) and nickel(II) with 1,10-phenantroline and 2,2'-bipyridine have been investigated towards the superoxide radical using the nitro blue tetrazolium chloride (NBT) test and the cyclic voltammetry (CV). Moreover, the biological activity of the complexes under study has been investigated in the Human Dermal Fibroblasts adult (HDFa) cell line. In the first step, the cytotoxic and the antiproliferative activities of the complexes were examined. Subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…109472 Россия, г. Москва, ул. Академика Скрябина, 23, e-mail: kochish.i@mail.ru, tommi@list.ru , azarena@list.ru Поступила в редакцию 28 A b s t r a c t Hypoxic manifestations, including those associated with certain periods of bird embryogenesis, lead to slowdown in development, and in severe cases, to multifaceted morphological and functional disorders in embryos. Numerous studies have confirmed the effectiveness of biostimulants with pronounced antioxidant properties, which can neutralize negative effects of hypoxia and provide conditions for a faster transition to aerobic glycolysis.…”
Section: фгбоу во московская государственная академия ветеринарной ме...mentioning
confidence: 99%
See 1 more Smart Citation
“…109472 Россия, г. Москва, ул. Академика Скрябина, 23, e-mail: kochish.i@mail.ru, tommi@list.ru , azarena@list.ru Поступила в редакцию 28 A b s t r a c t Hypoxic manifestations, including those associated with certain periods of bird embryogenesis, lead to slowdown in development, and in severe cases, to multifaceted morphological and functional disorders in embryos. Numerous studies have confirmed the effectiveness of biostimulants with pronounced antioxidant properties, which can neutralize negative effects of hypoxia and provide conditions for a faster transition to aerobic glycolysis.…”
Section: фгбоу во московская государственная академия ветеринарной ме...mentioning
confidence: 99%
“…Сообщалось о важной роли кобальта для образования азотистых оснований, формирования первичной структуры РНК и ДНК, синтеза аминокислот, интенсивности метаболизма углеводов и липидов (19,20,23). Также доказано, что органические соединения кобальта участвуют в реакциях, подавляющих синтез свободных радикалов, в избытке образующихся при стрессах (24)(25)(26)(27)(28)(29).…”
unclassified
“…The values of percent superoxide anion scavenging by curcumin and its derivatives are presented in Table 1. [28] 0.05 9.45 * For compound 11, it was not possible to select the concentration in which the formation of the product with the radical anion would not interfere with the measurement of absorbance at 560 nm.…”
Section: Low Concentration Of Synthesized Derivatives Of Curcumin Showed Antioxidant Effectmentioning
confidence: 99%
“…The substitution reaction of complex compounds with special promoters may occur in acidic (the promoters are H + ions) or basic (the promoters are OHions) media or may be induced with Fe 3+ ions. [1][2][3][4][5][6][7][8] Polycarboxylic anions are a group of organic compounds which are used in coordination chemistry as ligands, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] because they stabilize metal ions in solutions 14 and, moreover, they are noncytotoxic. 15 Furthermore, the polycarboxylate coordination compounds of cobalt(II), nickel(II), 12,16,18 oxidovanadium(IV), 15,17 and copper(II) 19,20 have interesting antioxidant, antibacterial, and antifungal activities.…”
Section: Introductionmentioning
confidence: 99%